The teaching of frozen expressions through the graphic novel Persépolis - Sclafani, Marie-Denise (Verbum, 2019)
The constant search for suitable teaching materials to achieve the linguistic skills provided by a language teaching course, finds in authentic documents an important instrument for teaching foreign languages. The scientific literature attesting to the effectiveness of the authentic material is wide and consolidated; indeed, a text conceived by a native for a native, and, therefore, not developed for the sole purpose of teaching a foreign language, is intrinsically carrying a cultural richness and a linguistic variety, which are rarely present in any didactic artifact. The authentic material therefore represents an opportunity to meet the fixed expressions that are part of the communicative potential of a language; their teaching is not always taken into account, or is considered, at most, as a positive side effect of the natural process of linguistic acquisition. A communicative act for it to be effective must be able to be understood by the interlocutor ; it is therefore necessary to ensure not only grammatical accuracy and correct pronunciation, but also the understanding and use of frozen sequences. The graphic novel can offer the opportunity to benefit from an authentic language rich in idiomatic expressions, because the effectiveness of dialogues is a transposition of the language spoken in everyday life and familiar expressions. The article aims to show the didactic advantages of a graphic novel in the teaching of the French language. We explain the importance of the text-image relationship and the potential of the verbal language of the graphic novel, and we talk about the need to learn frozen expressions for a good command of the language and the distinctive aspects specific to comics that contribute to their understanding and learning; we show, finally, how the adoption, within the framework of a contrastive analysis of the language, of the graphic novel Persépolis by Marjane Satrapi could help the students to understand more easily the fixed expressions
Keywords: graphic novel; french language teaching; frozen expressions